A Novel Source of Methylglyoxal and Glyoxal in Retina: Implications for Age-Related Macular Degeneration - Yoon, Kee Dong (Public Library of Science, 2012)
Aging of retinal pigment epithelial (RPE) cells of the eye is marked by accumulations of bisretinoid fluorophores; two of the compounds within this lipofuscin mixture are A2E and all-trans-retinal dimer. These pigments are implicated in pathological mechanisms involved in some vision-threatening disorders including age-related macular degeneration (AMD). Studies have shown that bisretinoids are photosensitive compounds that undergo photooxidation and photodegradation when irradiated with short wavelength visible light. Utilizing ultra performance liquid chromatography (UPLC) with electrospray ionization mass spectrometry (ESI-MS) we demonstrate that photodegradation of A2E and all-trans-retinal dimer generates the dicarbonyls glyoxal (GO) and methylglyoxal (MG), that are known to modify proteins by advanced glycation endproduct (AGE) formation. By extracellular trapping with aminoguanidine, we established that these oxo-aldehydes are released from irradiated A2E-containing RPE cells. Enzyme-linked immunosorbant assays (ELISA) revealed that the substrate underlying A2E-containing RPE was AGE-modified after irradiation. This AGE deposition was suppressed by prior treatment of the cells with aminoguanidine. AGE-modification causes structural and functional impairment of proteins. In chronic diseases such as diabetes and atherosclerosis, MG and GO modify proteins by non-enzymatic glycation and oxidation reactions. AGE-modified proteins are also components of drusen, the sub-RPE deposits that confer increased risk of AMD onset. These results indicate that photodegraded RPE bisretinoid is likely to be a previously unknown source of MG and GO in the eye.